2000
DOI: 10.1046/j.1365-2958.2000.01717.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and biochemical evidence of a Campylobacter jejuni capsular polysaccharide that accounts for Penner serotype specificity

Abstract: Campylobacter jejuni, a Gram‐negative spiral bacterium, is the most common bacterial cause of acute human gastroenteritis and is increasingly recognized for its association with the serious post‐infection neurological complications of the Miller–Fisher and Guillain–Barré syndromes. C. jejuni lipopolysaccharide (LPS) is thought to be involved in the pathogenesis of both uncomplicated infection and more serious sequelae, yet the LPS remains poorly characterized. Current studies on C. jejuni suggest that all stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
278
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(293 citation statements)
references
References 77 publications
12
278
1
2
Order By: Relevance
“…5). Our data are consistent with the acapsular phenotype of a kpsS insertion mutant in C. jejuni (44) and with the loss of polysaccharide transport in E. coli and Neisseria meningitidis kpsS mutants (20,85). In contrast, transposon insertions in Cj1431c, Cj1432c, and Cj1437c did not result in the loss of CPS (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…5). Our data are consistent with the acapsular phenotype of a kpsS insertion mutant in C. jejuni (44) and with the loss of polysaccharide transport in E. coli and Neisseria meningitidis kpsS mutants (20,85). In contrast, transposon insertions in Cj1431c, Cj1432c, and Cj1437c did not result in the loss of CPS (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The CPS can be seen in the wild type as a collection of bands migrating about midway into the gel. A kpsM insertional mutant is known to be acapsular (44,77) and was included in the gel as a negative control. While strains bearing transposon insertions in Cj1413c (kpsS) and Cj1442c appear to be acapsular, strains with insertions in Cj1437c, Cj1431c, and Cj1432c still express CPS, although a subtle change in CPS migration is apparent in the Cj1432c mutant.…”
Section: Vol 74 2008 Steady-state Acid Stress Response Of C Jejunimentioning
confidence: 99%
“…Adherence involves different types of lectin-like molecules attaching to their corresponding glycosylated receptors on the epithelial cells (Guerry et al, 2002). Major outermembrane proteins such as the putative rod-shapedetermining protein MreB, the putative periplasmic protein MreC and C. jejuni lipoprotein JlpA play important roles in bacterial adhesion (Ashgar et al, 2007;del Rocio Leon-Kempis et al, 2006;Jin et al, 2003;Kakuda & DiRita, 2006;Karlyshev et al, 2000;Konkel et al, 1997;Linton et al, 2000;Mamelli et al, 2006;McSweegan & Walker, 1986;Monteville & Konkel, 2002;Moser et al, 1997;Pei & Blaser, 1993). The genes encoding these three proteins were upregulated in response to MUC2.…”
Section: Muc2 Concn (Mg MLmentioning
confidence: 99%
“…Therefore, O-acetylation appears to be a near final step of decorating the serogroup A capsular polymers. Cell-surface hydrophobicity, a marker of capsule expression, measured by hydrophobic interaction column chromatography (23), showed that the mynC mutant cell surface was hydrophilic (Ͻ5% cells retained on the column) and was similar to the wild-type parent (Ͻ4% cells retained on the column). In contrast, the unencapsulated variant F8239 (Ͼ60% cells retained on the column) and the mynA and mynB mutants (Ͼ90% cells retained on the column) demonstrated high cellsurface hydrophobicity.…”
Section: Figmentioning
confidence: 99%